Efeitos da urbanização na sub-bacia do Ribeirão Barra Nova - Apucarana-PR - Segantim, Leonardo Pereira (2023)
Urbanization in Brazil has increased considerably in recent decades due to factors such as the search for employment, access to health systems, education and agricultural mechanization. This accelerated growth has led to numerous infrastructure problems, as the organization of cities was not prepared to receive the population demand. As the population grew, changes to the natural environment also became evident. The creation of the urban river environment resulted from the sealing off of areas, including street paving, building construction, roofs, parking lots, among others, which resulted in a reduction in concentration times and an increase in peak flows. This has affected the hydrological cycle and the dynamics of water resources. The magnitude of these changes depends on the characteristics of each location, such as soil type, vegetation cover, rainfall and climate. In addition to changes in the course of water bodies, urbanization has caused population growth and concentration, leading to excessive use of natural resources and environmental pollution, generating numerous environmental impacts. In this context, this research is justified, as its objective was to analyze the effects of urbanization on the Ribeirão Barra Nova sub-basin, in the municipality of Apucarana-PR. In order to assess the physical alterations to the stream, methods were used to define and assess the morphometric characteristics, apply the Rapid Assessment Protocol for Urban Rivers (PARU) at seven sampling points, assess the stability of the hydraulic structures and study the use and occupation of the sub-basin. As a result of the application of the PARU, it was found that the general condition of the Barra Nova stream, at the points observed, varies from regular to recovered, with the worst condition being identified at local 3, reaching an average of 31 points in this stretch due to the degraded situation of the banks, the absence of riparian forest and the presence of solid waste throughout the area. The area at local 5 received a total score of 87 points, being classified as 'excellent', as the site is characterized by the presence of pasture fields and plantations, without the interference of the urban environment. The sub-basin has a more elongated morphometric characteristic, with low rates of flooding due to the longer time of concentration. Five hydraulic structures were identified along the course of the Barra Nova stream, two of which had a 'regular' level of stability. These areas were also assessed using the FHWA protocol. The land use and land cover of the Barra Nova stream sub-basin area shows an increase from 18 to 49% of the built-up area over 30 years. This growth was noticeable in the horizontal direction, especially when there was a rural exodus and a decrease in arable land. It was found that all the locals evaluated show some level of degradation, and urgent measures are needed to reverse this situation, favoring the preservation of the Barra Nova stream in Apucarana-PR and all the life forms around it.